FEATURES OF QUALITY OF LIFE IN PRIMARY SCHOOL CHILDREN IN THE REHABILITATION PERIOD OF ACUTE RESPIRATORY VIRAL INFECTIONS - Артем Михайлович Левчин; Ирина Борисовна Ершова; Оксана Васильевна Петренко (Мать и дитя в Кузбассе)
The aim of the research – the study of the quality of life (QOL) of primary school students who returned to education in the early period of convalescence of acute respiratory viral infection (ARVI).